2014
DOI: 10.1002/adem.201400007
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Low Friction on 100Cr6‐Steel Surfaces After Direct Laser Interference Patterning

Abstract: This study discusses the effects of surface topographies on the frictional behavior of 100Cr6 bearing steel. A solid state laser with nanosecond pulses is used to produce one-and two-dimensional periodic micropatterns using direct laser interference patterning. Line-, cross-, and dot-like patterns with pitches of 5 mm, and aspect ratios (AR) between 0.02 and 0.17 are fabricated. The friction tests of the surface textured samples are performed under lubricating conditions using a ball-on-disk configuration in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 40 publications
(45 reference statements)
0
21
0
2
Order By: Relevance
“…Former studies about DLIP of metallic surfaces, utilizing ns‐pulsed laser irradiation, showed a limitation in the feasible maximal structure depth up to values of approximately 0.2 times the spatial pitch ( Λ ), especially for pitches below 2 μm . This effect was explained due to the significant decrease of the temperature difference between interference maxima and minima positions, since the heat provided by the laser has enough time to diffuse to the minima by thermal conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Former studies about DLIP of metallic surfaces, utilizing ns‐pulsed laser irradiation, showed a limitation in the feasible maximal structure depth up to values of approximately 0.2 times the spatial pitch ( Λ ), especially for pitches below 2 μm . This effect was explained due to the significant decrease of the temperature difference between interference maxima and minima positions, since the heat provided by the laser has enough time to diffuse to the minima by thermal conduction.…”
Section: Introductionmentioning
confidence: 99%
“…This method enables the large‐scale fabrication of complex structures by systematically varying the dimensions of the gratings superimposed upon each other. Another significant advantage of DLIP compared with other surface patterning methods is that fairly large areas can be processed within a short period of time (up to several cm 2 /s) using single or multiple laser pulses …”
Section: Introductionmentioning
confidence: 99%
“…For instance, it can be used to improve adhesion between metals and epoxy resin [39,40], but also for precision material cutting and/or drilling [36] on a variety of materials including composites [59,54,43]. Moreover, it has been recently employed to enhance the tribological behavior of steel and diamond coatings [41,58].…”
Section: Introductionmentioning
confidence: 99%